2022
DOI: 10.1002/ange.202208570
|View full text |Cite
|
Sign up to set email alerts
|

Arene‐Ruthenium(II)/Osmium(II) Complexes Potentiate the Anticancer Efficacy of Metformin via Glucose Metabolism Reprogramming

Abstract: Targeting metabolic reprogramming to treat cancer could increase overall survival and reduce side effects. Here, we put forward a strategy using arene‐ruthenium(II)/osmium(II) complexes to potentiate the anticancer effect of metformin (Met.) via glucose metabolism reprogramming. Complexes 1–6 with oxoglaucine derivatives as ligands were synthesized and their anti‐tumor activities were tested under hypoglycemia. Results indicated that 2 and 5 potentiated the anticancer effects of Met. under hypoglycemia, exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Several research investigations demonstrated the importance of metal complexes in glucose metabolism under standard physiological settings. [50][51][52][53] As a result, we investigated the effect of our synthesized ligand and its transition metal complexes on glucose metabolism in the human breast cancer cell line MDA-MB-231. Following that, we investigated if these complexes regulate the metabolic activity in MDA-MB-231 cells by altering glucose uptake and metabolism.…”
Section: Anti-cancer Studymentioning
confidence: 99%
“…Several research investigations demonstrated the importance of metal complexes in glucose metabolism under standard physiological settings. [50][51][52][53] As a result, we investigated the effect of our synthesized ligand and its transition metal complexes on glucose metabolism in the human breast cancer cell line MDA-MB-231. Following that, we investigated if these complexes regulate the metabolic activity in MDA-MB-231 cells by altering glucose uptake and metabolism.…”
Section: Anti-cancer Studymentioning
confidence: 99%